2022
DOI: 10.32479/ijefi.13431
|View full text |Cite
|
Sign up to set email alerts
|

Revisit of Tunisia’s Money Demand Function: What About Oil Price and Exchange Rate Effects?

Abstract: This paper examines the long run and short run dynamic relationship between real broad money and macroeconomic factors in Tunisia for the period 2010M01 to 2019M07. We employ linear and NARDL bound testing approach for co-integration between the money demand measure and its determinants. Three real broader money demand variables (M2, M3, and M4) are considered to show that exchange rate have asymmetric significant effects once we introduce nonlinearity in the long run as well as in the short run association. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This phenomenon can be explained by the theory of "Effective Wealth", which suggests that an increase in oil prices can increase the wealth of oil-producing countries, stimulating investment and financial transactions (Hamilton, 1983). In addition, the literature highlights the influence of oil revenues on the financial system and investment, supporting the idea that changes in the price of oil can affect financial activity (Kilian and Park, 2009;Tala and Hlongwane, 2023;Sharma and Dahiya, 2023;Neifar and Kammoun, 2022).…”
Section: Resultsmentioning
confidence: 87%
“…This phenomenon can be explained by the theory of "Effective Wealth", which suggests that an increase in oil prices can increase the wealth of oil-producing countries, stimulating investment and financial transactions (Hamilton, 1983). In addition, the literature highlights the influence of oil revenues on the financial system and investment, supporting the idea that changes in the price of oil can affect financial activity (Kilian and Park, 2009;Tala and Hlongwane, 2023;Sharma and Dahiya, 2023;Neifar and Kammoun, 2022).…”
Section: Resultsmentioning
confidence: 87%
“…This resonates with the argument that as a result of the oil dependent nature of GCC states, their economies become very sensitive to oil price fluctuations (Maghyereh et al, 2020;Jawadi and Ftiti, 2019; Gray 2011). To clearly highlight similar studies on the GCC region, other studies have also studied the relationship of oil price fluctuations on GDP growth and on income sustainability as well as other impacts of oil price on microeconomic variables of a country (Murshed et al, 2020;Chang et al, 2020;Tala and Hlongwane, 2023;Balcilar et al, 2019;Badeeb and Lean, 2018;Basher et al, 2018;Neifar and Kammoun, 2022;Sharma and Dahiya, 2023;Salisu and Oloko, 2015;Musa 2010). In another related study Nasir et al, (2019) revealed the impact of oil price on macroeconomic variables in GCC member countries between 1980-2016. the studies mentioned above observed a heterogenous response of GCC member countries on oil price shocks.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, oil exporting countries benefit from high oil prices (Tuzova and Qayum, 2016;Abdelsalam, 2023;Bagadeem, 2023;Neifar and Kammoun, 2022). For them, although oil shocks positively impact economic growth, the negative impact can be very large.…”
Section: Literature Reviewmentioning
confidence: 99%